Analysis of the Influence of Green HR on Employee Job Satisfaction in Eco-Friendly Hotels in Lake Toba with Work Environment as an Intervening Variable - Frederick Rudy Sentosa Rajagukguk; Indra Welly Arifin; Hastuti Handayani Harahap (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the effect of Green HR on the Work Environment and Job Satisfaction of employees in environmentally friendly hotels around Lake Toba, as well as the effect of Harmonization of Digitalization of Tax Accounting on Community Economic Welfare through Digital Literacy. The results of the study indicate that the implementation of Green HR policies has a significant effect on the quality of the work environment and employee satisfaction. Sustainability-based and environmentally friendly policies increase motivation and work comfort, which in turn increases employee satisfaction. In addition, the digitalization of tax accounting, supported by digital literacy, has a positive impact on improving community economic welfare. These findings support the theory that policies that prioritize sustainability, both in the fields of HR and taxation, can create better results in improving quality of life and work productivity. This study makes an important contribution to the development of policies that support sustainability and digitalization in improving economic welfare and job satisfaction.